Can lean management change the managerial culture in higher education?. Issue 4 (3rd April 2022) - Cano, Michele; Murray, Rowena; Kourouklis, Athanassios
ABSTRACT: Problems associated with managerialism are well established in Higher Education. Driven by pressures of funding cuts, league tables and the associated competitive environment, Higher Education followed other public sector bodies in adopting Lean Management principles. While there is scepticism about Lean Management because it is seen as an instrument of managerialism, it is a philosophy that can resolve issues created by the managerialism movement. It offers ways of working with reduced resources without increasing pressure on staff. This paper proposes a Lean Management framework for Higher Education that focusses on creating value for stakeholders rather than cost-cutting. This framework was developed through a grounded theory approach, examining key features, successes and lessons learned from established programmes. This study shows that the framework could benefit universities and resolve some of the problems associated with managerialism.